Impact of a community based health‐promotion programme in 2‐ to 9‐year‐old children in Europe on markers of the metabolic syndrome, the IDEFICS study. (December 2015) - Mårild, S.; Russo, P.; Veidebaum, T.; Tornaritis, M.; De Henauw, S.; De Bourdeaudhuij, I.; Molnár, D.; Moreno, L. A.; Bramsved, R.; Peplies, J.; Ahrens, W.; ,
Summary: Introduction: One objective of 'Identification and prevention of Dietary‐and lifestyle‐induced health EFfects In Children and infantS', the IDEFICS study, was to implement a community‐oriented childhood obesity prevention intervention in eight European countries. Objective: To assess the effect of an obesity primary prevention programme on metabolic markers. Methods: The study had a non‐randomized cluster‐experimental design. In each country, children were recruited from distinct communities serving as intervention and control regions. Health examinations were done during 2007–2008 before the intervention (T0 ) and during 2009–2010 (T1 ). Children with results available from T0 and T1 on blood pressure, waist circumference and at least one blood‐marker (fasting glucose, insulin, HOMA‐IR, HbA1c, HDL‐ and LDL‐cholesterol, triglycerides, C‐reactive protein) were included. A metabolic syndrome (MetS) score was calculated. Results: A total of 7, 406 children (age 2–9.9 years) of the 16, 228 participating at T0 provided the necessary data. No effect of the intervention was seen on insulin, HOMA‐IR, CRP or the MetS score. Overall fasting glucose increased less in the intervention than in the control region, a pattern driven by three of the eight countries and more pronounced in children of parents with low education. Overall, HbA1c and waist circumference increased more and blood pressure less in the intervention regions. Conclusion: We observed no convincing effect of the intervention on markers of the metabolic syndrome. We identified diverse patterns of change for several markers of uncertain relation to the intervention. © 2015 World Obesity